A Framework For Monitoring And Modelling Of Btex In Various Development Statuses In Penang, Malaysia. - Al Madhoun, Wesam Ahmed; Ramli, Nor Azam; Yahaya, Ahmad Shukri; Md Yusuf, Noor Faizah Fitri; Ghazali, Nurul Adyani; Sansuddin, Nurulilyana (2008)

(untitled)
The development and urbanization process in Malaysia are believed to contribute to the deterioration of air quality. The rapid growth of the Malaysian economy lead to the increase of motor vehicles ownership, in 2006, there 6.91 million registered cars running on the roads in Malaysia. Benzene, Toluene, Ethylbenzene and Xylene (BTEX) form an important group of aromatic Volatile Organic Compounds (VOCs), emitted mainly from cars, where BTEX is a known carcinogenic.